Braking and performance characteristics of experienced and inexperienced mountain bikers navigating an isolated off-road turn using a brake power meter - Miller, M. C.; Fink, P. W.; Macdermid, P. W.; Allen, D.; Stannard, S. R. (International Journal of Performance Analysis in Sport, 2018)
Using a brake power meter, experienced and inexperienced mountain bikers were tested on an isolated, controlled off-road cycling descent with a turn to determine how riding experience affects the pattern of braking behaviour. Overall braking measurements such as absolute and relative brake work and brake power, as well as brake time, were significantly related to performance time on the track used in this study. Inexperienced mountain bikers displayed greater absolute and relative brake work and brake time, but had lower absolute and relative brake power when compared with experienced mountain bikers, which resulted in a significant performance decrement for inexperienced riders. Experienced mountain bikers concentrated braking efforts to later in the track, which meant that they spent less time at lower speeds. Inexperienced riders displayed a greater reliance on the rear brake, which likely contributed to their overall increased braking variables. The results of this study highlight that differences in braking magnitude and behaviour are attributable to reduced performance on an isolated off-road track with a corner. Inexperienced mountain bike riders may be able to improve their performance by learning braking patterns similar to those of experienced mountain bikers.